Preceramic, Aceramic or Early Ceramic? The radiocarbon dated beginning of the Neolithic in the Aegean - Agathe Reingruber (Documenta Praehistorica, 2015)
The Pre-Pottery-Neolithic refers to a period in the Eastern Mediterranean when ceramic containers were not yet in use (although small objects made of clay were already being created). This concept, which reflects a specific and quite unique stage in the development of human history, was introduced to Aegean prehistory under the term of Preceramic during the 1950’s (e.g., in Argissa Magoula and Sesklo). Shortly thereafter, a different term, the Aceramic, was applied in the Aegean (e.g., in Knossos) for levels devoid of pottery, although ceramic products were supposedly used in the wider region. In some cases, the thin levels interpreted as Preceramic or as Aceramic contained sherds that were regarded as being intrusive from above (e.g., Argissa-Magoula, Franchthi Cave). The new sequences of radiocarbon dates allow a more precise description of this early period and thereby contribute, not least, also to the clarification of terminological issues.